2019
DOI: 10.9758/cpn.2019.17.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intranasal Oxytocin in Anxiety and Depressive Disorders: A Systematic Review of Randomized Controlled Trials

Abstract: Several studies have demonstrated the neuromodulating function of oxytocin (OT) in response to anxiogenic stimuli as well as its potential role in the pathogenesis of depression. Consequently, intranasal OT (IN-OT) has been proposed as a potential treatment of anxiety and depressive disorders. The present systematic review aimed to summarize the randomized controlled trials (RCTs) evaluating the effect of IN-OT on anxiety and depressive symptoms. Overall, 15 studies were included, involving patients with socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(49 citation statements)
references
References 73 publications
0
43
0
Order By: Relevance
“… “A systematic literature search was performed in Web of Knowledge™ (including KCI Korean Journal Database, MEDLINE, Russian Science Citation Index, and SciELO Citation Index)….” [ 52 ] …”
Section: Part 3: Explanation and Elaborationmentioning
confidence: 99%
“… “A systematic literature search was performed in Web of Knowledge™ (including KCI Korean Journal Database, MEDLINE, Russian Science Citation Index, and SciELO Citation Index)….” [ 52 ] …”
Section: Part 3: Explanation and Elaborationmentioning
confidence: 99%
“…OXT exerts anxiolytic and antidepressant effects and modulates neuronal functions associated with stress responses 70 . For example, intranasal OXT treatment was shown to decrease HPA axis activity, anxiety- and depression-related symptoms 71 73 . Since there is a significant comorbidity between these disorders 74 , 75 , common mediators such as OXT are presumably to underlie both psychiatric disorders 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Although there are studies showing that oxytocin spray may decrease anxiety in humans, the recent systematic review of the randomized controlled trials (RCTs) demonstrated that the effect of OT spray on anxiety and depressive symptoms is still inconclusive (De Cagna et al, 2019 ).…”
Section: Importance Of Hypothalamic Oxytocin In Stressmentioning
confidence: 99%